Brochures and Newsletters - Ricky Telg (EDIS)
Brochures are small, usually folded documents used to inform, educate, or persuade the reader. They are commonly used to promote organizations, products, or events. Brochures attract attention through eye-catching designs. Brochures must contain clear, concise, focused writing because they are so short. When writing and designing a brochure, incorporating these recommendations can contribute greatly to your document’s overall effect. This 4-page fact sheet was written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.